Pemahaman dan Penanganan Kesulitan Membaca pada Anak-anak Kelas II: Studi Kasus di SD Negeri 54/I Bajubang - Anggun, Sonia; Lusi, Yanti Dwi; Puspitri, Mayangsari; Putri, Rosadi Dwi (TSAQOFAH, 2023)
This study aims to describe the reading challenges faced by second-grade students at SD Negeri 54/I Bajubang and the contributions of teachers in addressing these challenges. A descriptive qualitative methodology is employed in this research. Educators and second-grade students from SD Negeri 54/I Bajubang participated in this study. Interviewing, observation, and documentation are some of the data collection techniques employed. The collected data are analyzed using the Miles and Huberman model, which involves data reduction, data presentation, and drawing conclusions. Based on the findings, the reading comprehension issues among some second-grade students at SD Negeri 54/I Bajubang reached 70%. Students who struggle with reading often face difficulties in letter recognition, reading meaningful and meaningless words, reading fluently and comprehending the text, and listening or comprehending auditory information.